SoDA: A Sound Design Accelerator for the automatic generation of soundscapes from an ontologically annotated sound library - Koutsomichalis, Marinos; Valle, Andrea; Casu, Matteo; Armao, Paolo (My University, 2014)
In this paper we describe the SoDA project, that aims at automatically generating soundscapes from a database of annotated sound files. The rationale of the project lies in the ubiquitous requirement for sound designer to produce backgrounds that include specific multi-layered sound materials. SoDA provides an ontologically-annotated database that allows the sound designer to describe the desired soundscape by keywords: by referring to the database, the system then delivers a resulting audiofile.